Impact of adoption of fall armyworm and stemborer pest control practices on maize yields in Rwanda: A multinomial endogenous switching regression approach - Vincent Gadamba Misango; Jonathan Makau Nzuma; Patrick Irungu; Menale Kassie (Journal of Agriculture and Food Research)
The use of push-pull technologies (PPT) as an alternative control method for fall armyworms and stemborer pests amongst maize farmers has recently received considerable global attention. However, the impact of adoption of PPT on the maize productivity remains largely unexplored. This study used a multinomial endogenous switching regression (MESR) to evaluate the impact of adoption of PPT on smallholder maize farmer's yields in Rwanda. The MESR model was estimated on a sample of 398 households operating 967 maize plots selected using a stratified random sampling technique. Overall, 25, 20, and 14 percent of the households used traditional methods, PPT and pesticides respectively in isolation to control the two maize pests in Rwanda. Another 8 and 7 percent of the households used a combination of pesticides and traditional methods and a mix of PPT and traditional methods respectively. Adoption of PPT was significantly affected by the perceived technological benefits and farmers' demographic characteristics. Moreover, adoption of PPT in the control of FAW and stemborer pests significantly improved maize yields in Rwanda. Development initiatives should therefore focus on awareness creation of the perceived technology benefits and avail the technology to smallholder farmers in Rwanda.